Historical Study of Arab Village Tourism in Gresik: Transformation of Religious Tourism in the Post-Covid-19 Era - Santoso, Yuniawan Heru; Nuruddin, Nuruddin; Fiatiano, Edwin; Ismail, Muhammad Hussein (Journal of Business on Hospitality and Tourism, 2024)
The old city of Gresik is recognized for its Arab Kampong in Gapurosukolilo Village, home to the graves of the first harbor master and the first regent of Gresik. These sites have now become significant cultural heritage and pilgrimage tourism attractions. This study aims to investigate the conditions and impact of tourism in the Arab Kampong Gresik during the Covid-19 pandemic and to provide insights for the post-COVID-19 era. Employing a qualitative historical perspective, the research analyzes data from documents and interviews regarding past events. The findings reveal that during the pandemic, the number of tourists visiting the Arab Kampong of Gresik decreased, resulting in a substantial decline in the local community's income. The interpretation focuses on the processes of rethink, rebuild, and restart, which have led to the creation of strategic programs designed to assist the community in effectively navigating the challenges of the Post Covid-19 era.